2016
DOI: 10.1007/s12035-016-0108-8
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene Attenuates Early Brain Injury Following Subarachnoid Hemorrhage via Inhibition of the NLRP3 Inflammasome and Nox2-Related Oxidative Stress

Abstract: Pterostilbene (PTE), one of the polyphenols present in plants such as blueberries and grapes, has been suggested to have various effects, such as anti-oxidation, anti-apoptosis, and anti-cancer effects. Subarachnoid hemorrhage (SAH) is a severe neurological event known for its high morbidity and mortality. Recently, early brain injury (EBI) has been reported to play a significant role in the prognosis of patients with SAH. The present study aimed to investigate whether PTE could attenuate EBI after SAH was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 72 publications
6
77
0
Order By: Relevance
“…Further studies proved that pterostilbene also reduced NLRP3 inflammasome activation after subarachnoid hemorrhage induction. Besides, the protein levels of active caspase‐1, IL‐1β, and IL‐18 were markedly increased in brain tissues after the subarachnoid hemorrhage, and pterostilbene administration significantly reduced the expression levels . In the present study, we found that pterostilbene attenuated Aβ 1−42 ‐induced NLRP3/caspase‐1 inflammasome.…”
Section: Discussionsupporting
confidence: 63%
“…Further studies proved that pterostilbene also reduced NLRP3 inflammasome activation after subarachnoid hemorrhage induction. Besides, the protein levels of active caspase‐1, IL‐1β, and IL‐18 were markedly increased in brain tissues after the subarachnoid hemorrhage, and pterostilbene administration significantly reduced the expression levels . In the present study, we found that pterostilbene attenuated Aβ 1−42 ‐induced NLRP3/caspase‐1 inflammasome.…”
Section: Discussionsupporting
confidence: 63%
“…Apoptosis is regulated by the anti-apoptotic family and the pro-apoptotic family. Bcl-2, known as a key protein in the anti-apoptotic family, is localized in the outer membrane of mitochondria, and it plays an important role in promoting cellular survival and inhibiting the actions of pro-apoptotic proteins (20). It has been suggested that Bcl-2 can inhibit the release of cytochrome c, which can trigger apoptosis, from the mitochondria (21).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study supported the role of NLRP3 inflammasome in the development of DN. Two signals are required for full NLRP3 activation; the first is a TLR‐dependent activation of NF‐κB, which may be induced by extracellular HSP72, resulting in the upregulation of NLRP3 and pro‐IL‐1β expression (“priming”), and the second signal is NLRP3 activating signal which has been mechanistically linked with hyperglycemia and oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study supported the role of NLRP3 inflammasome in the development of DN. Two signals are required for full NLRP3 activation; the first is a TLR-dependent activation of NF-jB, which may be induced by extracellular HSP72, resulting in the upregulation of NLRP3 and pro-IL-1b IUBMB LIFE expression ("priming"), and the second signal is NLRP3 activating signal which has been mechanistically linked with hyperglycemia and oxidative stress (15,51,52). Recently, Elmonem et al suggested that NLRP3 inflammasome system may play an important role in the activation of CHIT1 expression, as IL-1b can directly or indirectly stimulate NF-jB signaling pathway and induce the production of tumor necrosis factor-a (TNF-a) thus stimulating the expression of CHIT1 (44).…”
Section: Discussionmentioning
confidence: 99%